Determining the Print Quality Due to Deformation of the Halftone Dots in Flexography - Dean Valdec (MDPI AG, 2021)
This paper researches the issues related to the print quality in flexography, especially the influence of the print run and inadequate printing settings on dot deformation. Dot deformation can lead to inconsistencies in print quality, such as a loss of highlight tones or an unpredictable increase in tonal value. This research was conducted on two concrete examples of flexible packaging printed on transparent films. All significant parameters of dot deformation were evaluated, including dot coverage, dot sharpness and the uniformity of the ink density. The increase in the coverage values in the midtones was linear throughout the entire print run, while in the light tones, it was more logarithmic. The overall percentage deviations from the reference value were 6.3% in the midtones and 52.6% in the light area. The increase in dot coverage was due to the wear of the polymer plate, which caused the side shoulders of the dot to become a part of the printing surface. An analysis of the ink density showed a much more homogeneous shape of the dot at the beginning of the print run. The correct ratio of the anilox roller line screen to the line ruling of the printing plate is important in order to ensure a minimum dot size in print.